تجليات البنية السردية في رواية "شياطين بانكوك" لعبد الرزاق طواهرية - عطااله, حسام الدين; بوقرحة, محمد; حداء, عبد الباسط (جامعة الوادي - university of Eloued, 2023)
لقد رصدت لنا رواية شياطين بانكوك حالة الشاب وخاصة الشباب المولع بالهجرة إلى الغرب؛ حيث يرون الغرب مكان تحقيق أحلامهم، ورغم هذا فقد طغى على الرواية تقنية الاسترجاع وهذا يدل علة أن البطل متعلق ومتمسك بماضيه في بلاده الجزائر، ونظرا للشخصية قيصر زرقي المضطربة كانت شخصية انطوائية يسودها الحزن والإكتئاب، حيث يعيش حياته في العالم الافتراضي أكثر مما يعيشه في عالمه الحقيقي، ولهذا وظف الكاتب الأماكن المنغلقة والداخلية بكثرة في الرواية، لقد أماطت لنا رواية شياطين بانكوك اللثام عن وهم السعادة والجنة في العالم الغربي. The Devils of Bangkok documented the case of the young man, especially the young man who is fond of emigrating to the West. Where they see the West as a place to realize their dreams, and despite this, the novel was dominated by the retrieval technique, and this indicates the reason that the hero is attached to and clings to his past in his country, Algeria, and given the troubled personality of Caesar Zarqi, he was an introverted personality dominated by sadness and depression, as he lives his life in the virtual world more than he lives in his world The real one, and for this reason the writer employed closed and internal places abundantly in the novel. The Devils of Bangkok revealed to us the illusion of happiness and paradise in the Western world
أدب حديث و معاصر
Keywords: الرواية، الشخصية، الزمان، المكان; novel, personality, time, place.